feat(frontends/lean/structure_cmd): allow structure declarations that contains only a header

This commit is contained in:
Leonardo de Moura 2014-11-03 22:17:43 -08:00
parent 91749d2364
commit 8f3139231b
2 changed files with 39 additions and 65 deletions

View file

@ -447,6 +447,12 @@ struct structure_cmd_fn {
elaborate_new_fields(new_fields); elaborate_new_fields(new_fields);
} }
void process_empty_new_fields() {
buffer<expr> new_fields;
elaborate_new_fields(new_fields);
}
/** \brief Traverse fields and collect the universes they reside in \c r_lvls. /** \brief Traverse fields and collect the universes they reside in \c r_lvls.
This information is used to compute the resultant universe level for the inductive datatype declaration. This information is used to compute the resultant universe level for the inductive datatype declaration.
*/ */
@ -684,13 +690,19 @@ struct structure_cmd_fn {
environment operator()() { environment operator()() {
process_header(); process_header();
m_p.check_token_next(get_assign_tk(), "invalid 'structure', ':=' expected"); if (m_p.curr_is_token(get_assign_tk())) {
m_mk_pos = m_p.pos(); m_p.check_token_next(get_assign_tk(), "invalid 'structure', ':=' expected");
m_mk = m_p.check_atomic_id_next("invalid 'structure', identifier expected"); m_mk_pos = m_p.pos();
m_mk = m_name + m_mk; m_mk = m_p.check_atomic_id_next("invalid 'structure', identifier expected");
m_mk_infer = parse_implicit_infer_modifier(m_p); m_mk = m_name + m_mk;
m_p.check_token_next(get_dcolon_tk(), "invalid 'structure', '::' expected"); m_mk_infer = parse_implicit_infer_modifier(m_p);
process_new_fields(); m_p.check_token_next(get_dcolon_tk(), "invalid 'structure', '::' expected");
process_new_fields();
} else {
m_mk_pos = m_name_pos;
m_mk = m_name + "mk";
process_empty_new_fields();
}
infer_resultant_universe(); infer_resultant_universe();
collect_ctx_locals(m_ctx_locals); collect_ctx_locals(m_ctx_locals);
add_ctx_locals(m_ctx_locals); add_ctx_locals(m_ctx_locals);

View file

@ -61,7 +61,7 @@ namespace comm_semigroup
binary.left_comm mul_comm mul_assoc a b c binary.left_comm mul_comm mul_assoc a b c
end comm_semigroup end comm_semigroup
structure monoid [class] (A : Type) extends semigroup A, has_one A:= structure monoid [class] (A : Type) extends semigroup A, has_one A :=
mk :: (right_id : ∀a, mul a one = a) (left_id : ∀a, mul one a = a) mk :: (right_id : ∀a, mul a one = a) (left_id : ∀a, mul one a = a)
section section
@ -73,70 +73,32 @@ section
theorem mul_left_id : 1 * a = a := !monoid.left_id theorem mul_left_id : 1 * a = a := !monoid.left_id
end end
exit structure comm_monoid [class] (A : Type) extends monoid A, comm_semigroup A
structure comm_monoid [class] (A : Type) extends monoid A, comm_semigroup A :=
mk ::
exit structure Semigroup :=
mk :: (carrier : Type) (struct : semigroup carrier)
namespace comm_monoid coercion Semigroup.carrier
section instance Semigroup.struct
variables {A : Type} [s : comm_monoid A]
variables a b c : A
definition mul := comm_monoid.rec (λmul one assoc right_id left_id comm, mul) s a b
definition one := comm_monoid.rec (λmul one assoc right_id left_id comm, one) s
definition assoc : mul (mul a b) c = mul a (mul b c) :=
comm_monoid.rec (λmul one assoc right_id left_id comm, assoc) s a b c
definition right_id : mul a one = a :=
comm_monoid.rec (λmul one assoc right_id left_id comm, right_id) s a
definition left_id : mul one a = a :=
comm_monoid.rec (λmul one assoc right_id left_id comm, left_id) s a
definition comm : mul a b = mul b a :=
comm_monoid.rec (λmul one assoc right_id left_id comm, comm) s a b
end
end comm_monoid
section structure CommSemigroup :=
variables {A : Type} [s : comm_monoid A] mk :: (carrier : Type) (struct : comm_semigroup carrier)
include s
definition comm_monoid_monoid [instance] : monoid A :=
monoid.mk comm_monoid.mul comm_monoid.one comm_monoid.assoc
comm_monoid.right_id comm_monoid.left_id
definition comm_monoid_comm_semigroup [instance] : comm_semigroup A :=
comm_semigroup.mk comm_monoid.mul comm_monoid.assoc comm_monoid.comm
end
-- bundled structures coercion CommSemigroup.carrier
-- ------------------ instance CommSemigroup.struct
inductive Semigroup [class] : Type := mk : Π carrier : Type, semigroup carrier → Semigroup structure Monoid :=
section mk :: (carrier : Type) (struct : monoid carrier)
variable S : Semigroup
definition Semigroup.carrier [coercion] : Type := Semigroup.rec (λc s, c) S
definition Semigroup.struc [instance] : semigroup S := Semigroup.rec (λc s, s) S
end
inductive CommSemigroup [class] : Type := coercion Monoid.carrier
mk : Π carrier : Type, comm_semigroup carrier → CommSemigroup instance Monoid.struct
section
variable S : CommSemigroup
definition CommSemigroup.carrier [coercion] : Type := CommSemigroup.rec (λc s, c) S
definition CommSemigroup.struc [instance] : comm_semigroup S := CommSemigroup.rec (λc s, s) S
end
inductive Monoid [class] : Type := mk : Π carrier : Type, monoid carrier → Monoid structure CommMonoid :=
section mk :: (carrier : Type) (struct : comm_monoid carrier)
variable S : Monoid
definition Monoid.carrier [coercion] : Type := Monoid.rec (λc s, c) S coercion CommMonoid.carrier
definition Monoid.struc [instance] : monoid S := Monoid.rec (λc s, s) S instance CommMonoid.struct
end
inductive CommMonoid : Type := mk : Π carrier : Type, comm_monoid carrier → CommMonoid
section
variable S : CommMonoid
definition CommMonoid.carrier [coercion] : Type := CommMonoid.rec (λc s, c) S
definition CommMonoid.struc [instance] : comm_monoid S := CommMonoid.rec (λc s, s) S
end
end algebra end algebra
open algebra open algebra
@ -156,7 +118,7 @@ calc
... = a * b * (c * d) : !mul_assoc ... = a * b * (c * d) : !mul_assoc
-- for test4b to work, we need instances at the level of the bundled structures as well -- for test4b to work, we need instances at the level of the bundled structures as well
definition Monoid_Semigroup [instance] (M : Monoid) : Semigroup := definition Monoid_Semigroup [coercion] (M : Monoid) : Semigroup :=
Semigroup.mk (Monoid.carrier M) _ Semigroup.mk (Monoid.carrier M) _
theorem test4 {M : Monoid} (a b c d : M) : a * (b * c) * d = a * b * (c * d) := theorem test4 {M : Monoid} (a b c d : M) : a * (b * c) * d = a * b * (c * d) :=